Phase II Study of Adjuvant Chemoradiotherapy Using Docetaxel/Cisplatin/5-Fluorouracil Before and After Intensity-modulated Radiotherapy With Concurrent Docetaxel in Patients With Completely (R0) Resected Gastric Carcinoma. (July 2018) - Liu, Yong; Zhao, Guoqi; Xu, Yi; Zhang, Tiening; Chen, Zhixiao; Yan, Ge; Tu, Wenzhi; Hu, Ye; Chen, Ying; He, Xia; Li, Xiaodong; Chen, Hui; et al.
Abstract : Objectives: The Intergroup 0116 study has demonstrated a significant survival benefit for completely resected (R0) gastric cancer patients treated with a fluorouracil/leucovorin chemoradiotherapy regimen. However, this regimen is also toxic and less effective in terms of distant disease control. Therefore, a more efficacious and safer regimen is urgently needed. Methods: Patients with R0 resected gastric carcinoma received up to two 21-day cycles of postoperative adjuvant preradiation and postradiation DCF chemotherapy (docetaxel 37.5 mg/m 2 on days 1 and 8, cisplatin 25 mg/m 2 on days 1 to 3, and a continuous infusion of fluorouracil 750 mg/m 2 on days 1 to 5), respectively. Chemoradiotherapy between preradiation and postradiation chemotherapy was initiated on day 43 and consisted of intensity-modulated radiotherapy (45 Gy) plus concurrent docetaxel 20 mg/m 2 weekly for 5 weeks. Results: A total of 55 patients were evaluated and 76% (42) of patients completed the prescribed therapy. With a median follow-up of 61 months, the 3- and 5-year progression-free survival rates were 67% (95% confidence interval [CI], 54%-80%) and 59% (95% CI, 46%-72%), respectively; and the 3- and 5-year overall survival rates were 72% (95% CI, 60%-84%) and 61% (95% CI, 48%-74%), respectively. The most common grade 3 or greater toxicity, during the chemotherapy phase, was neutropenia (24%). Common grade 3/4 toxicities during concurrent chemoradiotherapy were nausea (32%), vomiting (26%), fatigue (15%), and anorexia (19%). Conclusions: These results demonstrate that this adjuvant regimen is active with an acceptable toxicity profile. A randomized phase 3 trial comparing the Intergroup 0116 chemoradiotherapy regimen with this regimen is underway.